Printability in Multi-material Projection-Based 3-Dimensional Bioprinting - Chao-fan He; Tian-hong Qiao; Xu-chao Ren; Mingjun Xie; Qing Gao; Chao-qi Xie; Peng Wang; Yuan Sun; Huayong Yang; Yong He (Research)
Accurately reconstructing the intricate structure of natural organisms is the long-standing goal of 3-dimensional (3D) bioprinting. Projection-based 3D printing boasts the highest resolution-to-manufacturing time ratio among all 3D-printing technologies, rendering it a highly promising technique in this field. However, achieving standardized, high-fidelity, and high-resolution printing of composite structures using bioinks with diverse mechanical properties remains a marked challenge. The root of this challenge lies in the long-standing neglect of multi-material printability research. Multi-material printing is far from a simple physical assembly of different materials; rather, effective control of material interfaces is a crucial factor that governs print quality. The current research gap in this area substantively hinders the widespread application and rapid development of multi-material projection-based 3D bioprinting. To bridge this critical gap, we developed a multi-material projection-based 3D bioprinter capable of simultaneous printing with 6 materials. Building upon this, we established a fundamental framework for multi-material printability research, encompassing its core logic and essential process specifications. Furthermore, we clarified several critical issues, including the cross-linking behavior of multicomponent bioinks, mechanical mismatch and interface strength in soft–hard composite structures, the penetration behavior of viscous bioinks within hydrogel polymer networks, liquid entrapment and adsorption phenomena in porous heterogeneous structures, and error source analysis along with resolution evaluation in multi-material printing. This study offers a solid theoretical foundation and guidance for the quantitative assessment of multi-material projection-based 3D bioprinting, holding promise to advance the field toward higher precision and the reconstruction of more intricate biological structures.